Characterization of doped and undoped CuO nanoparticles - (:unkn) unknown (American Institute of Physics Inc., 2010)
Undoped and doped with Ti, Cd and Zn CuO nanoparticles were obtained by precipitation method. The crystal structures of the CuO nanoparticles were characterized by X-ray diffraction. Impedance spectroscopy (IS) and d.c conductivity (σd.c) measurements were performed on samples as a function of temperature and frequency (40-105 Hz.) to determine the electrical behavior of the nano powder. It was found that the Arrhenius graph of the samples consist of two linear regions and corresponding activation energies.The dependency of frequency exponent s on temperature and frequency suggests a conduction mechanism which is indication of hopping. The measured impedance spectra showed a furher semicircle at low frequencies for all temperatures. The low frequency semicirles in impedance spectra are attributted to the garin boundry effects. © 2009 American Institute of Physics.
Keywords: Ac conductivity; Capacitance; Impedance spectra